PRODUKSI ENZIM KITINASE MENGGUNAKAN ISOLAT JAMUR LOKAL TRICHODERMA ASPERELLUM TNC52 DENGAN PENGARUH LAJU AERASI - Saputra, Noris; Helianty, Sri; Rezeki, Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Chitinase is an enzyme that can transform chitin into N-acetylglucosamine (GlcNAc), which is very useful in the pharmaceutical, especially as an agent of anti-tumor and anti-cancer. This research is an enlarged scale of 25 mL enzyme production that already done with enzyme activity 0.0137 U / mL, an enlarged scale is already done in a bioreactor with volume of medium is 1.5 L with aeration, aeration is doing by pumping an air by sparger and assisted by stirrer with a stirring speed motors 40-60 rpm and aeration rate of 0.5 vvm; 1 vvm; 1.5 vvm and without aeration process. The best enzyme activity is produced at a rate of 1 vvm aeration and fermentation time is 8 days with time of inoculation starter is 5 days with the activity of an enzyme produced has analyze through UV-VIS spectrophotometer with a sugar content analysis method, Nelson-Somogyi.Keywords: aeration, chitinase, enzyme, inokulation, nelson-somogyi, sparger, starter